Trinidad and Tobago : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper analyzes the historical and current energy booms of Trinidad and Tobago, and points out the main policy issues during boom times. It provides practical suggestions on the long-term management of the expected resource windfall in Trinidad and Tobago, and outlines theoretical guidelines to calculate sustainable consumption out of energy wealth and targets sustainable levels of non-energy fiscal deficits. It discusses the developments, main policy issues in the state-owned nonfinancial enterprise sector, and the proposed restructuring plan for the state sugar company. It also provides a Statistical Appendix for Trinidad and Tobago.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet